2001
DOI: 10.1093/jnci/93.12.921
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor as a Genetic Therapy Target for Carcinoma Cell Radiosensitization

Abstract: Transduction of MDA-MB-231 xenograft tumors with Ad-EGFR-CD533 conferred a dominant-negative EGFR phenotype and induced tumor radiosensitization. Therefore, disruption of EGFR function through overexpression of EGFR-CD533 may hold promise as a gene therapeutic approach to enhance the sensitivity of tumor cells to ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 34 publications
2
49
1
1
Order By: Relevance
“…We have demonstrated previously (19) that ionizing radiation induced an immediate activation of EGFRwt in xenograft tumors, which showed a maximum activation within 10 minutes after a single 4-Gy radiation exposure. Thus, we investigated further the effects of ionizing radiation on EGFRvIII tyrosine phosphorylation in vivo.…”
Section: Expression Of Egfrviii In Malignant Gliomamentioning
confidence: 77%
See 2 more Smart Citations
“…We have demonstrated previously (19) that ionizing radiation induced an immediate activation of EGFRwt in xenograft tumors, which showed a maximum activation within 10 minutes after a single 4-Gy radiation exposure. Thus, we investigated further the effects of ionizing radiation on EGFRvIII tyrosine phosphorylation in vivo.…”
Section: Expression Of Egfrviii In Malignant Gliomamentioning
confidence: 77%
“…Our previous studies (19) have shown that expression of EGFR-CD533 reduced the basal and radiation-stimulated tyrosine phosphorylation of EGFRwt. In the present study, we examined whether expression of EGFR-CD533 could also modulate EGFRvIII activity.…”
Section: Expression Of Egfrviii In Malignant Gliomamentioning
confidence: 91%
See 1 more Smart Citation
“…This difference changed to a 2.5-fold increase in relative radioresistance of EGFRvIII expressing cells after 4 Gy. These data represent the most direct demonstration that radiation-induced activation of EGFR species provides a strong cytoprotective signal with increased radioresistance through enhanced proliferation and repair Reardon et al, 1999;Lammering et al, 2001a). From studies on p185neu (ERBB2), the impact of ERBB receptors on cellular radiosensitivity may not be limited to EGFR and its mutants (O'Rourke et al, 1997(O'Rourke et al, , 1998a, but likely depend upon the entire ERBB expression profile of a given tumor cell (Bowers et al, 2001;Lammering et al, 2001a;Contessa et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…To date, mechanistic studies on this naturally occurring truncated receptor have been limited since its spontaneous expression is only seen in vivo in naturally occurring tumors or xenografts of human tumor cells (Lammering et al, 2001a) and is rapidly lost in vitro (Bigner et al, 1990). In extension of previous studies on the role of EGFRvIII as an oncoprotein (Ekstrand et al, 1994;Nishikawa et al, 1994;Batra et al, 1995;Nagane et al, 1996;Huang et al, 1997), have started to define its involvement in cellular responses to genotoxic stress, such as ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%